Rational access to the idea of God - Aznar Sala, Francisco Javier (Razón y fe, 2022)
The idea of God has weakened in the collective imagination and there are fewer and fewer who follow it. There is no doubt that the positive revelation of the divine has remained only for those who claim to believe, but traditionally there were some paths of access to the divine that were marked out from philosophical work. The article intends to travel that path from cosmological and anthropological postulates, with the intention of establishing a bridge of strictly rational dialogue.
Keywords: divinity; knowledge; cosmology; anthropology; love